The effects of oil and gasoline prices on confidence and stock return of the energy companies for Turkey and the US - Bildirici, Melike E.; Badur, Mesut M. (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
This study aims to investigate the relationships between oil price, consumer confidence and stock return and between gasoline price, consumer confidence and stock return for Turkey and the US by using the Markov Switching Vector Auto Regressive (MS-VAR) method and the Markov Switching-Granger Causality (MS-GC) method. Some studies determined that gasoline prices respond asymmetrically to oil price changes. These variables are included in the study, since they may affect the confidence index in different ways. The study found two different results for Turkey and the US. The first difference is that there is a bidirectional causality between oil price and confidence index in the US in all regimes whilst there is a unidirectional relationship from oil price to confidence index in Turkey. The second difference between the results of the two countries is that although stock return of energy companies interact with confidence index and changes in oil prices in both countries, oil prices and gasoline prices have different causality relationships with confidence index in Turkey. Therefore, gasoline prices along with oil prices should also be included especially in future studies analyzing countries where gasoline price determining is part of the indirect tax policy. (C) 2019 Published by Elsevier Ltd.
Keywords: Consumer confidence; Economic confidence; Oil price; Gasoline price; Stock return; INVESTOR SENTIMENT; SHOCKS; Thermodynamics; Energy & Fuels